The Influence Of Work Motivation On Employee Performance At Paradigma Restaurant And Café, Cikini - Gita Putri, Octaviani (JELAJAH: Journal of Tourism and Hospitality, 2025)
This study aims to examine the influence of work motivation on employee performance at Paradigma Restaurant and Cafe, Cikini. The sample consisted of all Paradigma employees, totaling 32 individuals. Primary data was collected through observations and questionnaires, while secondary data was also utilized. The analytical method employed was a descriptive method with a quantitative approach, incorporating validity tests, reliability tests, descriptive statistics, the coefficient of determination test, correlation tests, and simple linear regression analysis. The findings indicate that the average score for the work motivation variable (X) was 3.14, placing it in the "excellent" category, suggesting that employees have high work motivation. Meanwhile, the average score for the performance variable (Y) was 3.37, categorized as "strongly agree," indicating that employee performance is very good. The correlation strength was found to be 72%, with a coefficient of determination of 52%, signifying a substantial relationship. The simple linear regression equation obtained was Y = 1.179 + 0.696X, concluding that work motivation positively impacts employee performance at Paradigma Restaurant and Cafe, Cikini.